An Application of Structured Decision Making Process in Approaching Deforestation and Promoting Sustainable Forest Management of Sylhet, Bangladesh - Zakaria, A. F. M. (Advances in Social Sciences Research Journal, 2020)
Deforestation is a global phenomenon with a critical recognition. It is very visible mostly in developing countries in Asia and Southern America. In many regions where forest loss is significant, so much effort has been garnered towards protecting the natural forest and promoting sustainable forest management (SFM). Evidence of such efforts includes the various policies, principles, and frameworks put in place both at the international and domestic levels. Despite these efforts, forest depletion continues to thrive at alarming rates particularly in developing countries like Bangladesh. This paper brings out a plethora of complex causes and consequences of deforestation in Sylhet, Bangladesh, with the principal objective of using a structured decision-making (SDM) approach to address deforestation in Sylhet through a pluralistic stakeholder engagement that represents all the objectives of the various groups in a very understandable manner. Mainly deploying FGD to consult with different stakeholder groups, representing different interests working through the steps of SDM, the consultations developed a SDM framework with suggested alternative approaches towards addressing deforestation in Sylhet, Bangladesh. Based on the judgments of the consultations, suitable policy options for addressing deforestation in Sylhet, Bangladesh should focus on maximizing forest management, minimizing dependence on forest resources, and Alternative ‘A’ (Safe guarding forest by improving forest management). This case study provides insights on how SDM can be implemented for SFM in Sylhet, as well as some challenges and opportunities encountered during the process.